Long-term outcomes after bladder-preserving tri-modality therapy for patients with muscle-invasive bladder cancer. (3rd June 2021) - Fabiano, Emmanuelle; Durdux, Catherine; Dufour, Bertrand; Mejean, Arnaud; Thiounn, Nicolas; Chrétien, Yves; Bibault, Jean-Emmanuel; Giraud, Philippe; Kreps, Sarah; Smulevici, Antoine; Maraadji, Safia; Housset, Martin
Abstract: Purpose: To evaluate trimodal conservative treatment as an alternative to radical surgery for urothelial muscle-invasive bladder cancer (MIBC). Patients and methods: This retrospective study reported the carcinologic and functional results of patients (pts) presenting a cT2/T3 N 0M0 operable MIBC and fit for surgery, treated by a conservative strategy. Treatment consisted of a transurethral resection (TURB) followed by concomitant bi-fractionated split-course radiochemotherapy (RCT) with 5FU-Cisplatine. A control cystoscopy was performed six weeks after the induction RCT (eq45Gy) with systematic biopsies. Patients with complete histologic response achieved RCT protocol. Salvage surgery was proposed to pts with persistent tumor. Results: 313 pts (83% cT2 and 17% cT3) treated between 1988 and 2013 were included, with a median follow-up of 59 months and 67-year mean age. After the induction RCT, the histologic response rate was 83%. After five years, overall, disease-free, and functional bladder-intact survival rates were respectively 69%, 61%, and 69%, significantly better for pts in complete response after induction RCT. Late urinary and digestive toxicities were limited, with respective rates of 4% and 1.5% of grade 3 toxicity. Conclusion: Trimodal strategy with RCT after TURB showed interesting functional and oncologic results and should be considered as an alternative to surgery in well-selected pts.